Chlorhexidine and silver-sulfadiazine coated central venous catheters in haematological patients—a double-blind, randomised, prospective, controlled trial - Ostendorf, Torben Armin; Meinhold, Andrea; Harter, Christoph; Salwender, Hans; Egerer, Gerlinde; Geiss, Heinrich K.; Ho, Anthony Dick; Goldschmidt, Hartmut (Supportive care in cancer, 2005)
Central venous catheters (CVCs) are essential for the intensive care of patients with haematological illness. Catheter-related infections (CRI) are an important problem in modern medicine, which may lead to life-threatening situations, to prolonged hospitalisation and increased cost. In immunocompromised patients suffering from haemato-oncological diseases, CRI is a significant factor for adverse outcome. Several clinical studies have shown that CVCs coated with antiseptics such as chlorhexidine and silver-sulfadiazine (CHSS) reduce the risk of catheter-related bacteraemia. Most studies, however, were performed on intensive care patients not suffering from chemotherapy-induced immunosuppression.